Perancangan Sistem E-Commerce MotoPart Berbasis Web dengan Metode Waterfall - Masdar Helmi; Ahmad Wahyudi; Bagus Rifai; Luthfi Ardeansyah R (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to develop MotoPart, an online marketplace application specifically designed to meet the demand for motorcycle spare parts in Indonesia. The background to the development of this application is the high demand for motorcycle spare parts along with the increasing number of two-wheeled vehicles, as well as various problems still frequently encountered in conventional distribution systems. These problems include limited access to genuine products, inefficiencies in the transaction process, and limited information regarding product availability. MotoPart was developed with the main goal of facilitating digital spare part buying and selling transactions that are easier, safer, and more efficient, as well as building an active, trusted, and integrated automotive ecosystem. In this research, a comprehensive system requirements analysis was conducted, covering functional requirements such as user registration and authentication, product management by sellers, a product search and filter system, a shopping cart feature, digital payments, delivery services, a user review system, notifications, transaction management, and an admin panel for monitoring. Meanwhile, non-functional requirements were also outlined to ensure system performance and reliability, including the required hardware and software specifications. The system design was carried out using a Data Flow Diagram (DFD) approach, starting from the context diagram to level 1 to illustrate the data flow and processes that occur. Furthermore, the database design was designed in detail with tables such as users, products, orders, and order items, to support systematic data management. With the development of MotoPart, it is hoped that it can provide solutions to obstacles in spare parts distribution, guarantee product authenticity, and become part of the digital transformation in the Indonesian automotive sector.